Accelerated aging and electrical conductivity tests in crambe seeds - Pereira Lima, Juliana Joice [UNESP]; Freitas, Marcella Nunes de; Guimaraes, Renato Mendes; Vieira, Antonio Rodrigues; Bento Avila, Maria Alice (Univ Federal Lavras-UFLA, 2015)
The aim of this study was to adapt the methodology of the accelerated aging and electrical conductivity tests for determination of physiological potential in crambe seeds. Six seed lots of crambe (cv. FMS Brilhante) were subjected to determination of moisture content, germination test, first count germination, emergence, and emergence speed index. For the accelerated aging test, the traditional methodology was used with water, and with a saturated potassium chloride and sodium chloride solution in three periods of exposure (24, 48, and 72 hours) at 41°C; the electrical conductivity test was performed with four pre-soaking treatments (0, 2, 4, and 8 hours) and four soaking periods (4, 8, 16, and 24 hours) at 25°C. The accelerated aging test with water for 72 hours and the electrical conductivity test with 2 hours of pre-soaking and assessment after 16 hours were effective for classification of the crambe seed lots in regard to physiological quality.

Conduziu-se esta pesquisa, com o objetivo de adequar a metodologia dos testes de envelhecimento acelerado e condutividade elétrica para determinação do potencial fisiológico em sementes de crambe. Seis lotes de sementes de crambe cultivar FMS Brilhante foram submetidos à determinação do teor de água, teste de germinação, primeira contagem de germinação, emergência, índice de velocidade de emergência. Para o teste de envelhecimento acelerado, foi utilizada a metodologia tradicional com o uso de água e com solução saturada de cloreto de potássio e cloreto de sódio em 3 períodos de exposição (24, 48 e 72 horas) a 41°C; o teste de condutividade elétrica foi realizado com quatro tratamentos de pré-embebição (0, 2, 4 e 8 horas) e quatro períodos de embebição (4, 8, 16 e 24 horas) a 25°C. O teste de envelhecimento acelerado com água por 72 horas e o teste de condutividade elétrica com 2 horas de pré- embebição e avaliação, após 16 horas, foram eficientes para a classificação dos lotes de sementes de crambe quanto à qualidade fisiológica.
Teste de envelhecimento acelerado e condutividade elétrica em sementes de crambe
Keywords: Crambe abyssinica; Vigor; Physiological quality; Crambe abyssinica; Vigor; Qualidade fisiológica